2015
DOI: 10.17795/ijep27372
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Pattern and Biofilm Formation Ability of Clinically Isolates of Salmonella enterica Serotype typhimurium

Abstract: Background:The emergence of antimicrobial-resistant bacteria with biofilm formation ability may be a major threat to public health and food safety and sanitation. Objectives: The aim of this study was to determine antibiotic resistance patterns and biofilm production characteristics of Salmonella typhimurium isolated from different species of birds. Materials and Methods:The antibiotic resistance patterns of 38 pre-identified isolates were screened by standard Kirby-Bauer discdiffusion method performed on Muel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
6
2
Order By: Relevance
“…In the present study, biofilm formation abilities of Salmonella isolates, recovered from red meat (beef and mutton) and meat contact surfaces at retails, were studied. All isolates had the ability to form biofilms, most of them (75.86%) were moderate, and the rest were strong biofilm producers, which was more different from other reports that showed most of the tested isolates were weak biofilm producers (Díez‐García, Capita, & Alonso‐Calleja, 2012; Ghasemmahdi et al., 2015; Nair et al., 2015). Chuah et al.…”
Section: Resultscontrasting
confidence: 70%
“…In the present study, biofilm formation abilities of Salmonella isolates, recovered from red meat (beef and mutton) and meat contact surfaces at retails, were studied. All isolates had the ability to form biofilms, most of them (75.86%) were moderate, and the rest were strong biofilm producers, which was more different from other reports that showed most of the tested isolates were weak biofilm producers (Díez‐García, Capita, & Alonso‐Calleja, 2012; Ghasemmahdi et al., 2015; Nair et al., 2015). Chuah et al.…”
Section: Resultscontrasting
confidence: 70%
“…Also both positive and negative biofilm formation were showed same degree of mortality and morbidity, Signs of depression, diarrhea, Omphilitis in young chicks, perhepatitis, pericarditis, Oophritis, redness in brain. The obtained results were agree with (Wang et al, 2013) who reported that no significant correlation between antimicrobial resistance and biofilm production as well as agree with (Ghasemmahdi et al, 2015) who demonstrated that all Salmonella typhimurium isolates showed a high multiple antibiotic resistant with low biofilm formation capabilities which proposed low association between biofilm formation and antibiotic resistance of a major food important pathogen. As well as the results were agree with (Apellanis et al, 2017) who reported that no relationship was found between biofilm production and antimicrobial resistance in Salmonella enteritidis strains.…”
Section: Resultssupporting
confidence: 91%
“…These results were inconsistent with those reported from Turkey (34); but in agreement with the current study findings, a study conducted in Brazil showed the resistance about 88.8% to nalidixic acid (35). Also, Ghasemmahdi et al showed the resistance (97%) to nalidixic acid (36).…”
Section: Discussionmentioning
confidence: 99%